How important is precautionary labor supply? - Robin Jessen; Davud Rostam-Afschar; Sebastian Schmitz (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
We quantify the importance of precautionary labor supply using data from the German Socio-Economic Panel (SOEP) for 2001-2012. We estimate dynamic labor supply equations augmented with a measure of wage risk. Our results show that married men choose about 2.5% of their hours of work or one week per year on average to shield against unpredictable wage shocks. This implies that about 26% of precautionary savings are due to precautionary labor supply. If self-employed faced the same wage risk as the median civil servant, their hours of work would reduce by 4%.
Keywords: D91; J22; C23; 330; Wage Risk; Labor Supply; Precautionary Saving; Life Cycle; Dynamic Panel Data